Aging of enteric neuromuscular systems in gastrointestinal tract. Issue 6 (13th March 2022) - Nguyen, Vy Truong Thuy; Taheri, Negar; Chandra, Abhishek; Hayashi, Yujiro
Abstract: Background: Aging is a complex biological process and associated with a progressive decline in functions of most organs including the gastrointestinal (GI) tract. Age‐related GI motor disorders/dysfunctions include esophageal reflux, dysphagia, constipation, fecal incontinence, reduced compliance, and accommodation. Although the incidence and severity of these diseases and conditions increase with age, they are often underestimated due in part to nonspecific and variable symptoms and lack of sufficient medical attention. They negatively affect quality of life and predispose the elderly to other diseases, sarcopenia, and frailty. The mechanisms underlying aging‐associated GI dysfunctions remain unclear, and there is limited data examining the effect of aging on GI motor functions. Many studies on aging‐associated changes to cells within the tunica muscularis including enteric neurons, smooth muscles, and interstitial cells have proposed that cell loss and/or molecular changes may be involved in the pathogenesis of age‐related GI motor disorders/dysfunctions. There is also evidence that the aging contributes to phenotypic changes in innate immune cells, which are physically and functionally linked to other cells in the tunica muscularis and can alter GI (patho) physiology. However, various patterns of changes have been reported, some of which are contradictory, indicating a need for additional work in this area. Purpose: Although GI infection due to intestinal bacterial overgrowth, bleeding, and cancers are also important and common problems in the elderly patients, this mini‐review focuses on data obtained from enteric neuromuscular aging research with the goal of better understanding the cellular and molecular mechanisms of enteric neuromuscular aging to enhance future therapy.